Yearbook of the European Convention on Human Rights/Annuaire de la convention europeenne des droits de l'homme, Volume 46 (2003) (Human Rights and Humanitarian Law - Book Archive 2000-2005., 2004)
This volume of the Yearbook of the European Convention on Human Rights , prepared by the Directorate of Human Rights of the Council of Europe, relates to 2003. Part one contains information on the Convention. Part two deals with the control mechanism of the European Convention on Human Rights: selected judgments of the European Court of Human Rights and human rights (DH) resolutions of the Committee of Ministers; part three groups together the other work of the Council of Europe in the field of human rights, and includes the work of the Committee of Ministers, the Parliamentary Assembly and the Directorate General of Human Rights; part four is devoted to information on national legislation and extracts from national judicial decisions concerning rights protected by the Convention. Appendix A contains a bibliography on the Convention, and Appendix B the biographies of the new judges elected to the European Court of Human Rights.